2021
DOI: 10.1186/s12935-021-02327-7
|View full text |Cite
|
Sign up to set email alerts
|

Distinct associations of NEDD4L expression with genetic abnormalities and prognosis in acute myeloid leukemia

Abstract: Background There is mounting evidence that demonstrated the association of aberrant NEDD4L expression with diverse human cancers. However, the expression pattern and clinical implication of NEDD4L in acute myeloid leukemia (AML) remains poorly defined. Methods We systemically determined NEDD4L expression with its clinical significance in AML by both public data and our research cohort. Moreover, biological functions of NEDD4L in leukemogenesis were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…CREB/CRTC2 [26] and miR-1 [27] can regulate NEDD4L expression through transcriptional regulation, while AUF1 [28] and 14-3-3 protein [29] regulate its expression via post-transcriptional regulation, thereby affecting biological functions. NEDD4L variation is discovered in nervous system tumors (like glioma) [30], respiratory system tumors (like lung cancer) [31], digestive system tumors (including gastric cancer, liver cancer, pancreatic cancer and intestinal cancer) [32][33][34], endocrine target organ tumors (breast cancer, ovarian cancer, cervical cancer and prostatic cancer) [35][36][37][38], and hematologic system tumors (leukemia and multiple myeloma) [39,40], which has affected the progression of these tumors. We collected 117 esophageal carcinoma and para-carcinoma tissue samples from Jiangsu University Affiliated People's Hospital and confirmed through Western blot and immunohistochemistry that, the expression of NEDD4L in ESCC tissue was markedly lower than that in para-carcinoma tissues.…”
Section: Discussionmentioning
confidence: 99%
“…CREB/CRTC2 [26] and miR-1 [27] can regulate NEDD4L expression through transcriptional regulation, while AUF1 [28] and 14-3-3 protein [29] regulate its expression via post-transcriptional regulation, thereby affecting biological functions. NEDD4L variation is discovered in nervous system tumors (like glioma) [30], respiratory system tumors (like lung cancer) [31], digestive system tumors (including gastric cancer, liver cancer, pancreatic cancer and intestinal cancer) [32][33][34], endocrine target organ tumors (breast cancer, ovarian cancer, cervical cancer and prostatic cancer) [35][36][37][38], and hematologic system tumors (leukemia and multiple myeloma) [39,40], which has affected the progression of these tumors. We collected 117 esophageal carcinoma and para-carcinoma tissue samples from Jiangsu University Affiliated People's Hospital and confirmed through Western blot and immunohistochemistry that, the expression of NEDD4L in ESCC tissue was markedly lower than that in para-carcinoma tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in the NEDD4L gene also affect the prognosis of patients with NSCLC, and a bioinformatic analysis reported that in patients with NSCLC, the NEDD4L rs11660748 A>G and rs73440898 A>G adjusted overall survival hazard ratios were 1.31 and 1.27, respectively, implying that mutations in these two loci may affect patient prognosis (Yang S. et al, 2020). In AML, low NEDD4L expression is significantly associated with younger age at disease onset, higher leukocyte count, and higher numbers of naïve bone marrow/peripheral cells in patients (Chu et al, 2021). Moreover, multivariate analysis shows that NEDD4L expression is an independent prognostic factor in patients with gastric cancer (Gao et al, 2012;Jiang et al, 2019), squamous lung cancer (Sakashita et al, 2013) and glioma (He et al, 2012).…”
Section: Correlation In Nedd4l Gene Status Expression and Prognosismentioning
confidence: 98%
“…NEDD4L mRNA was expressed at low levels in acute myeloid leukemia (AML), and low expression was associated with a normal karyotype and Frontiers in Pharmacology frontiersin.org with FLT3 and NPM1 mutations. Additionally, low expression positively correlated with complex karyotypes and TP53 mutations, suggesting that aberrant NEDD4L expression is associated with multiple genetic events in AML (Chu et al, 2021).…”
Section: Low Nedd4l Expressionmentioning
confidence: 98%
See 2 more Smart Citations